PERAN WWF ARCTIC PROGRAMME DALAM MENANGGULANGI PENCAIRAN ES DI KUTUB UTARA - Fitri Hany Riesa; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The release of greenhouse gases from burning fossil fuels and other sources is causing temperatures in the Arctic to warm at twice the rate worldwide, resulting in lower sea ice, melting ice sheets and rising sea levels worldwide.The Arctic region has been the main focus of many climate change studies in recent years, both because of the many changes seen in the Arctic. Changes in temperature are the main cause of many changes that occur in the Arctic. WWF worked to ensure that development in the Arctic region did not destroy habitat and established the WWF Arctic Program focusing on the Arctic region. The purpose of writing is to provide general information about the Arctic as an area experiencing ice melt and provide an explanation of the role of the WWF Arctic Program in tackling ice melt in the Arctic.This paper uses the theory of the International Organization in which the actor involved is WWF, where the WWF Arctic Program collaborates with several countries to achieve the overall goal of stopping and repairing environmental damage that occurs in the North Pole. This study also uses descriptive qualitative research methods with secondary sources and data based on books, journals, and online literature such as reports, newspapers, and official articles from WWF.The results of the study indicate that the programs created by the WWF Arctic Program are long-term programs, so that currently no significant results have been seen from these programs. WWF develops standards and planning tools to ensure that the industry's footprint in the Arctic does not burden an already weakened ecosystem while recognizing that northern communities need the economy. WWF is also working to create a rules-based environment, where international rules on how Arctic resources should be managed are agreed upon and enforced. WWF also has a dedicated workflow to reduce the main threat to biodiversity in the Arctic, namely climate change. KeyWords: Arctic, WWF, WWF Arctic Programme, Renewable Energy